Warming enhances the cadmium toxicity on macrophyte Myriophyllum aquaticum (Vell.) Verd. seedlings - Wang, Lei; Gao, Yuxuan; Wang, Xuan; Qin, Zhangyi; Liu, Baogui; Zhang, Xinhou; Wang, Guoxiang (Environmental pollution (1987), 2021)
Due to a close contact with water column, submerged macrophytes are easily disturbed by environment change in freshwater ecosystems, especially at the seedling stage. In recent decades, freshwater ecosystems have been subject to severe cadmium (Cd) pollution, which can cause toxic effects on the growth of submerged macrophytes. Moreover, the temperature rise resulting from climate warming and water level decline may further aggravate such effect, especially in shallow lakes. Here, we investigated the independent and interaction effects of Cd exposure levels (0, 0.5, 1, and 2.5 mg L−1) and temperature (15, 25, and 30 °C) on morphological and physiological traits of Myriophyllum aquaticum (Vell.) Verd. Seedlings generated from propagules and seeds. The temperature rise and Cd exposure generally resulted in a significant increase of Cd concentrations and antioxidant enzyme activities in leaves, as well as a decrease of chlorophyll a and b concentrations. The number and length of leaves generated from propagules always show a downward trend with the increase of Cd exposure, regardless of the temperature. Moreover, the lowest leaf number and length always occurred at high temperature (i.e. 30 °C) when the Cd exposure level increased to 1 and 2.5 mg L−1. For the seedlings generated from seeds, the temperature rise caused an increase of leaf emergence rate under low Cd exposure levels, but resulted in a significant decrease with the Cd exposure level. This study indicates the negative effects of Cd exposure and temperature rise on submerged macrophytes at the seedling stage, and highlights that temperature rise would enhance Cd toxicity. [Display omitted] •The rise of temperature and Cd exposure level increased Cd accumulation in leaves.•High temperature and Cd exposure have negative effects on physiological traits.•The lowest leaf number and length occurred at high temperature × high Cd exposure.•Temperature rise would aggravate Cd toxicity on Myriophyllum aquaticum.•The seedlings from seeds have no advantage to cope with Cd over the propagules.